Hydrogen from renewable power : technology outlook for the energy transition (International Renewable Energy Agency, 2018)
As the world strives to cut carbon emissions, electric power from renewables has emerged as a vital energy source. Yet transport and industry will still require combustible fuels for many purposes. Such needs could be met with hydrogen, which itself can be produced using renewable power. Hydrogen provides high-grade heat, helping to meet a range of energy needs that would be difficult to address through direct electrification. This could make hydrogen the missing link in the transformation of the global energy system. Key sectors for renewable-based hydrogen uptake include: Industry, where it could replace fossil-based feedstocks, including natural gas, in high-emission applications. Buildings and power, where it could be mixed with natural gas or combined with industrial carbon dioxide (CO2) emissions to produce syngas. Transport, where it can provide low-carbon mobility through fuel-cell electric vehicles.
Keywords: Hydrogen as fuel.; Energy transition.; elektronické knihy; electronic books